Gc-Ms Determination Of Bioactive Constituents Of Cycas Beddomei Cones - N. RAVI KUMAR,; J.SATYANARAYAN REDDY,; G. GOPIKRISHNA,; K.ANAND SOLOMON, (International Journal of Pharma and Bio Sciences, 2012)
Cycas beddomei Dyer is one of the medicinally important plants belonging to the family Cycadaceae. In the present study, the methanolic extract of the cones of Cycas Beddomei analyzed by GC-MS, while the mass spectra of the compounds found in the extract was matched with the National Institute of Standards and Technology (NIST) library. Twelve phytochemical constituents have been identified. The major chemical constituents are 1, 3-Propanediol, 2-(hydroxymethyl)-2-nitro (61.14%), Methyl tetradecanoate (4.77%), Hexadecanoic acid, methyl ester (9.00%) and Methyl cis-7-octadecenoate (4.73 %).